UHPC sandwich panels with GFRP shear connectors tested under combined bending and axial loads. (1st December 2021) - Sylaj, Valon; Fam, Amir
Highlights: Ultra-high Performance Concrete (UHPC) led to very thin (25 mm) wythes in sandwich panel. GFRP bars in the form of diagonal grid provides very low thermal bridging shear connector. Panels tested under combined axial compression and bending to establish interaction curve. Degree of composite action reduced as axial compression increased and more connectors fail. Panel met requirements for highest wind pressure in the National Building Code of Canada. Abstract: A new design of double wythe insulated wall panels using ultra-high performance concrete (UHPC) and glass fibre-reinforced polymer (GFRP) shear connectors is developed and tested. It consists of two 25 mm thick UHPC ribbed wythes with a 152 mm thick layer of extruded polystyrene (XPS) sandwiched in between. Small diameter (4 mm) GFRP bars were used as reinforcements in the wythes and as diagonal shear connectors. Five 3.0 × 0.61 × 0.2 m panels were tested to failure in flexure (M), under axial compression (P) and under combined loading. Four-point bending was used to simulate wind pressure, while axial compression was applied on one wythe only, representing gravity floor loading. For combined loading, a constant (P) of 16%, 33% or 66% of the axial strength of the wall was applied on three different panels, then transverse loading was applied to failure. The full (P-M) interaction curves, relative to the centroids of a composite and non-composite sections were developed, including both primary and secondary moments from slenderness. The degree of composite action was calculated to be 78% under transverse loading only and was reduced as the axial load increased. Failure was triggered by a progressive fracture of the diagonal GFRP shear connectors, regardless of the M and P combination. The wall design met serviceability requirements at the highest wind pressure based on the 50-year return period as per the National Building Code of Canada.